Corner Detection Using Multi-directional Gabor Filters (Journal of Fiber Bioengineering and Informatics, 2015)
Exploiting the characteristics of corner, an information entropy-based corner detection algorithm usingthe multi-directional Gabor filters is proposed in this paper. Different from the methods which detectcorners by analyzing plane curve contour shape or finding for local maxima of curvature, the proposedmethod combines with the gray level changing information at edge contour pixels and pixels around thecontour pixels to find corner . Firstly, the Canny edge operator is used to extract edge map and the gapsin the edge map are filled. Secondly, the imaginary parts of Gabor filters are used to smooth the edgepixels and their surrounding pixels along multi-directions. Finally, the gradient direction informationentropy at the edge pixels is used to detect corners. Experimental results show that the proposedalgorithm attains better detection performance, higher localization accuracy and noise robustness thanthe existing several algorithms.
Keywords: Corner Detection; Imaginary Parts of the Gabor Filter; Gradient Direction Information Entropy